2001
DOI: 10.1063/1.1379534
|View full text |Cite
|
Sign up to set email alerts
|

The transition from oxygen chemisorption to oxidation of ultra-thin Ni layers on Cu(111)

Abstract: X-ray photoelectron spectroscopy (XPS) was used to study the initial stages of surface oxidation of pseudomorphic Ni monolayers on Cu(111). Oxygen was adsorbed at 150 K followed by annealing the sample to 300 K and 600 K, respectively. For oxygen coverages between 0.4 ML and 2.0 ML we find little change in the peak shapes of the O 1s XPS signal. The Ni 2p3/2 spectra change, however, drastically: the onset of the oxidation is marked by the appearance of a peak doublet shifted with respect to the peak of metalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…We thus conclude that the 529.2 eV species, which we identify as NiO, , is located beneath the 531.1 eV species. It was previously reported that chemisorbed oxygen on Ni(111) has the same peak position as in NiO, , but instead of the symmetric peak profile characteristic of semiconductors and insulators, the line shape is asymmetric for the chemisorbed species due to the interaction of chemisorbed oxygen with the high d-density of states at the Fermi level in metallic Ni . To confirm this finding, we formed a p(2×2) oxygen structure on Ni(111) and could indeed observe the asymmetric line shape in this control experiment, shown in Figure S3 along with the corresponding LEED pattern.…”
Section: Resultssupporting
confidence: 76%
“…We thus conclude that the 529.2 eV species, which we identify as NiO, , is located beneath the 531.1 eV species. It was previously reported that chemisorbed oxygen on Ni(111) has the same peak position as in NiO, , but instead of the symmetric peak profile characteristic of semiconductors and insulators, the line shape is asymmetric for the chemisorbed species due to the interaction of chemisorbed oxygen with the high d-density of states at the Fermi level in metallic Ni . To confirm this finding, we formed a p(2×2) oxygen structure on Ni(111) and could indeed observe the asymmetric line shape in this control experiment, shown in Figure S3 along with the corresponding LEED pattern.…”
Section: Resultssupporting
confidence: 76%
“…Moreover, the absence of a component located at ca. 852 eV 52 indicates that Ni 0 species were not present on the surface of 5Ni-beta both before and after reaction. Parallel to the decline with time-on-stream of the catalytic activity and the intensity of the Ni 2+ -and H + -related carbonyl bands we also observed the development of IR bands, resistant to evacuation, characteristic of CH3 and CH2 groups 34,[53][54][55] that evidence the formation of acyclic hydrocarbon species ( Figure S6) irreversibly adsorbed (hence, playing the role of spectators) on both the nickel cations and the Brønsted acid sites of 5Ni-beta.…”
Section: Results and Discussion Elucidation Of The Active Nickel Sitementioning
confidence: 99%
“…Their O 1s binding energies are found approximately 1 eV below that of NiO (529.4-529.6 eV; refs. [58], [59], [60] and [61]) and other binary transition metal oxides [52].…”
Section: Resultsmentioning
confidence: 99%